An Overview of The Open-Circuit Voltage Thermodynamics on Vanadium Redox Flow Battery and Zn-Air Redox Flow Battery - Ulsak, Mohammad Ghimnastiar; Ananda, Lintang Rizkyta; Sobarsah, G. Awaludin; Titani, Fena Retyo (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2026)
The open circuit voltage's Nernst equation, which was first developed Walther Nernst more than a hundred years earlier, is essential to the study of electrochemical systems. Regretfully, adapted to complex methods (such as interactions with mixed potentials or ion-exchange membranes), the equation takes on erroneous forms due to the assumptions that underlie its derivation being frequently ignored in the literature. Regardless of how the electrochemical processes are expressed, these errors may be prevented by using an accurate thermodynamic derivation. In particular, the Nernst equation must be correctly derived in order to describe zinc-air batteries and vanadium redox flow batteries. Non-equilibrium thermodynamics is where the rigorous route where the Nernst equation's formulation starts.